Adventures in the orgasmatron how the sexual revolution came to America - Turner, Christopher 1972- (Farrar, Straus and Giroux, 2011)
The untold story of the dawn of the sexual revolution in America-- an illuminating, startling, at times bizarre, story of sex and science, ecstasy and repression.